The urgency of developing digital-based media in Indonesian language learning - Amanda, Dea (Jurnal Penelitian Humaniora, 2025)
In the context of continuously evolving education, the utilization of digital technology in Indonesian language learning has become an essential necessity. The development of digital-based media in Indonesian language learning is of utmost importance to enhance the effectiveness and quality of the learning process. This study aims to examine the role of digital media in supporting the achievement of Indonesian language learning objectives in a more engaging, interactive, and effective manner. The research method used in this study is a literature review to collect and analyze various relevant sources related to the development of digital media in education. The findings indicate that the use of digital media can enhance students' learning motivation, support the development of 21st-century skills, and provide broader access to more flexible learning materials. However, challenges related to infrastructure and digital literacy still need to be addressed to fully maximize the potential of digital media. Therefore, developing digital media in alignment with the Merdeka curriculum and the needs of Indonesian language learning is crucial to improving the effectiveness of education in this digital era.